Effects of lead on growth, yield and mineral nutrition of rice (Oryza sativa L.) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
A pot experiment was conducted to evaluate the effect of lead (50, 100, 150 and 200 mg kg-1) on rice (Oryza sativa) and remediation of metal contamination by applying cow dung, poultry litter and lime to alleviate lead toxicity. The lengths, fresh and dry weights of shoot, root and macronutrients decreased with increasing level of lead compared to the control. The maximum reduction was observed in the pots treated with 200 mg kg-1 lead (19.50 and 20.03% for grain, 17.15 and 19.75% for shoot and 17.96 and 30.02% for root on the fresh and dry weight, respectively). The highest reduction in macronutrient content was observed in 200 mg kg-1 lead treated pot where N, P, K, Ca and Mg concentrations were reduced by 31.14, 47.44, 22.49, 21.84 and 31.58% for shoot and 28.95, 55.64, 37.5, 49.33 and 23% for root, respectively. On the other hand lead concentration in roots and shoots were increased with increasing lead treatment compared to the control. Treatments of the amendments (cow dung, poultry litter and lime) had positive effects though cow dung outshining the rest of them. This particular organic matter had considerable decreasing impacts in lead uptake by rice. Cow dung treated pots increased fresh and dry weight by 31.48 and 32.07% for grain, 14.08 and 35.30% for shoot and 57.09 and 34.48% for root compared to pot treated with 100 mg kg-1 lead. Cow dung remediated lead concentration by 48.85, 65.00 and 62.00% for grain, shoot and root, respectively.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 83-92